The Excess Sensitivity of Layoffs and Quits to Demand - Hall, Robert E.; Lazear, Edward P. (Journal of Labor Economics, 1984)
Excessive layoffs in bad times and excessive quits in good times both stem from the same weakness in practical employment arrangements: the specific nature of worker-firm relations creates a situation of bilateral monopoly. Institutions which have arisen to avert the associated inefficiency cannot mimic the separation decisions of a perfect-information, first-best allocation rule. Simple employment rules based on predetermined or indexed wages are in many cases the most desirable among the class of feasible employment arrangements. More complicated contracts which seem to deal more effectively with turn-over issues either are infeasible because of informational requirements or create adverse incentives on some other dimension.